2015
DOI: 10.1002/sej.1201
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Dynamics of Strategic Decision Making in Venture Creation: A Process Study of Effectuation and Causation

Abstract: The process of new venture creation is characterized by the need to decide and take action in the face of uncertainty. Especially in the context of technology-based ventures uncertainty is substantial, posing difficulties for strategic decision-making based on prediction and planning. and how entrepreneurs' emphasis on these logics shifts and re-shifts over time. From our data, we induce a dynamic model which extends the literature on strategic decision-making in venture creation, illustrating how external and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
371
1
19

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 315 publications
(409 citation statements)
references
References 72 publications
18
371
1
19
Order By: Relevance
“…Our findings are in line with Reymen et al () in that the HRD approaches we observed follow a hybrid decision‐making logic that uses both effectuation and causation simultaneously. Reymen et al () suggest that the optimal decision results “from a combination of both logics, where the causal logic ensures that the venture stays focused and predicts what is predictable, while effectual decision‐making allows responding flexibly to changing circumstances and maintaining hands‐on control over uncertain aspects of the venture.” In our dataset, we could not analyze shifts; we could only see that the dominant logic in the different groups of interviewees (entrepreneurs in firms in an early stage vs., later stage) is different. Additionally, our findings indicate that both firm age and firm size influence the HRD approach entrepreneurs apply, but an analysis of an interaction between the firms' age and size was not possible in our research design.…”
Section: Implications and Limitationssupporting
confidence: 92%
See 2 more Smart Citations
“…Our findings are in line with Reymen et al () in that the HRD approaches we observed follow a hybrid decision‐making logic that uses both effectuation and causation simultaneously. Reymen et al () suggest that the optimal decision results “from a combination of both logics, where the causal logic ensures that the venture stays focused and predicts what is predictable, while effectual decision‐making allows responding flexibly to changing circumstances and maintaining hands‐on control over uncertain aspects of the venture.” In our dataset, we could not analyze shifts; we could only see that the dominant logic in the different groups of interviewees (entrepreneurs in firms in an early stage vs., later stage) is different. Additionally, our findings indicate that both firm age and firm size influence the HRD approach entrepreneurs apply, but an analysis of an interaction between the firms' age and size was not possible in our research design.…”
Section: Implications and Limitationssupporting
confidence: 92%
“…Showing that the distinction between effectuation and causation helps to describe entrepreneurs' HRD approaches indicates that effectuation not only describes firm‐level decisions of entrepreneurs but also their HRD approach. Furthermore, previous research suggested causation and effectuation do not exclude each other but can exist concurrently (Reymen et al, ). Our findings support this notion, as we find that entrepreneurs combine causation and effectuation logic when deciding about HRD.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In the third step, inspired by the approach in Reymen et al (), we determined patterns of causation and effectuation over time by calculating the moving averages of the use of both logics. When an event was coded with one or more codes for the effectuation dimensions, it was marked as 1 for the effectuation category.…”
Section: Methodsmentioning
confidence: 99%
“…Research on dynamics in decision‐making recently revealed how effectual and causal logics are combined in a venture's strategic decision‐making (rather than one logic being used exclusively) and how emphasis on the use of these logics shifts over time. Effectuation is more dominant in early phases of development, whereas causation is more dominant in later stages (Berends et al, ; Reymen et al, ). The dominant decision‐making logic may shift several times (Reymen et al, ) and both decision‐making logics may co‐exist according to the different degrees of uncertainty in the market and technology, or the number of decision‐makers involved (Nummela et al, ).…”
Section: Theorymentioning
confidence: 99%